The Trichoptera of Lord Howe Island, including 3 new species, larvae and keys - Wells, Alice (Zootaxa, 2011)
Three new Trichoptera (caddisfly) species are described for the small south-western Pacific seamount island of Lord Howe, all probably endemics. These are 2 hydropsychids, Cheumatopsyche erskinensis sp. nov. and C. howensis sp. nov., and a leptocerid, Symphitoneuria neboissi sp. nov. These are the first species recorded from Lord Howe in the respective genera and increase to 5 the number of genera recorded from the island, and to 9 the number of named species. Features of 2 distinctive but unidentified Cheumatopsyche larvae, larval cases of S. neboissi sp. nov., and the larva and case of Tasiagma eremica Neboiss are illustrated and described. Life stages of species in 3 other genera are recorded from the island: several larvae and females identified as Ulmerochorema (Hydrobiosidae); 2 females of a species of Triplectides (Leptoceridae); and a larva of Plectrocnemia (Polycentropodidae), which is illustrated. Although, conceivably, none of these 3 has permanent populations, the 3 genera are included in the checklist of Trichoptera of Lord Howe Island and in the identification keys provided for Trichoptera adults and larvae of the island.